2021
DOI: 10.1007/s13205-020-02613-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of chickpea chlorotic dwarf virus and peanut witches’ broom phytoplasma associated with chickpea stunt disease and identification of new host crops and leafhopper vectors in India

Abstract: An investigation was carried out to identify and characterize the phytoplasma and viruses associated with the chickpea varieties showing severe stunting, leaf reddening, yellowing and phyllody symptoms during the summer season of 2018–2019 and 2019–2020 in eight states of India. The average disease incidence was recorded from 3 to 32% in different states. The presence of chickpea chlorotic dwarf virus (CpCDV) was confirmed in thirty-seven chickpea samples by amplification of CpCDV coat protein gene and sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Among major biotic stresses, chickpea stunt is the major disease caused by different groups of viruses, e.g. cucumovirus, mastrevirus and polerovirus, reported in many chickpea growing countries worldwide (Akram et al, 2016;Abraham et al, 2006;Chalam et al, 1986;Kanakala et al, 2013;Kanakala and Kuria, 2019;Shreenath et al, 2020;Reddy et al, 2021). The chickpea chlorotic dwarf virus (CpCDV) is widespread in all chickpea growing states of India (Horn et al, 1993;Kanakala et al, 2013;Shreenath et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among major biotic stresses, chickpea stunt is the major disease caused by different groups of viruses, e.g. cucumovirus, mastrevirus and polerovirus, reported in many chickpea growing countries worldwide (Akram et al, 2016;Abraham et al, 2006;Chalam et al, 1986;Kanakala et al, 2013;Kanakala and Kuria, 2019;Shreenath et al, 2020;Reddy et al, 2021). The chickpea chlorotic dwarf virus (CpCDV) is widespread in all chickpea growing states of India (Horn et al, 1993;Kanakala et al, 2013;Shreenath et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CpCDV and phytoplasma are reported to be transmitted by the leafhopper Orosius albicinctus in a persistent manner (Horn et al, 1993;Akhtar et al, 2011). In a recent study, CpCDV was identified in two species of leafhoppers, Amarasca (Sundapteryx) biguttula and O. albicinctus feeding in chickpea fields, suggesting that these leafhopper species may be potential source of natural vectors of CpCDV infection (Reddy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop is cultivated with an area of 9.93 Mha and a productivity of 935.34 kg/ha in India (Merga and Haji, 2019). The major chickpea growing states are Madhya Pradesh (MP), Rajasthan, Maharashtra,Uttar Pradesh (UP), Andhra Pradesh (AP), Karnataka, Chhattisgarh, Bihar, Tamil Nadu and Jharkhand.These states contribute more than 95% of the chickpea production in India (Pradipa et al, 2018;Gurivi Reddy et al, 2021).In Tamil Nadu, the crop is cultivated in districts of Coimbatore, Tiruppur, Dindigul, Thiruvallur, Kancheepuram, Erode, Salem, Namakkal, Perambalur, Tiruchirappali, Madurai, Virudhunagar, Ramanathapuram, Thoothukkudi, Tirunelveli and Dharmapuri (Pradipa et al, 2018). The crop loss due to biotic and abiotic stress has been reported for several years.…”
Section: Introductionmentioning
confidence: 99%
“…The chief symptoms reported by several workers associated with phytoplasma disease include stunting of plants, dwarfing, bushy appearance and leaf reddening. The plants infected in the early stages, it produced severe stunting symptoms (Shreenath et al, 2020;Gurivi Reddy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%